Bioprospecting of four Beauveria bassiana strains and their potential as biological control agents for Anastrepha ludens Loew 1873 (Diptera: Tephritidae) - Norberto A. Angel-Ruiz; Inés Zavala-Izquierdo; Diana Pérez-Staples; Francisco Díaz-Fleisher; Antonio Andrade-Torres; Griselda K. Guillén-Navarro; Pablo Colunga-Salas (PLoS ONE, 2025)
Anastrepha ludens (Loew) is a pest of major importance on mango and orange crops. The use of biological control agents, including entomopathogenic fungi (EPF), has been widely studied. However, one problem with the use of EPF is that the efficacy of the strains varies with environmental conditions, and thus the use of native strains is suggested. Therefore, the objective of the present study was to bioprospect Beauveria bassiana strains from Veracruz, Mexico and determine their potential as biological control agents for A. ludens. Four strains isolated from infected insects were used to calculate conidium viability percentage, growth rate mycelia, and conidium production in three different media: with rice, with empty A. ludens pupae, and with PDA. The median lethal time (LT50) and median lethal concentration (LC50) of these strains were also calculated in A. ludens adults exposed to concentrations of 105, 106, and 107 conidia/ml. The viability percentage ranged between 88%−98%, and the growth rate was higher in the rice media, with a value of 2.63 mm/day. However, conidium production was higher in the PDA and A. ludens pupae media, with values of 1.18x108 and 7.83x107 conidia/ml, respectively. At the highest concentration, the four strains caused mortality above 80%, and at the lowest concentration, only one strain caused mortality above 50%. The lowest LT50 occurred on day 5.51 at the highest concentration. The present study expands our knowledge on the effect of B. bassiana strains on A. ludens. In conclusion, the four strains used showed optimal levels for their potential use as biological control agents against A. ludens.